2020
DOI: 10.1027/1864-1105/a000271
|View full text |Cite
|
Sign up to set email alerts
|

The Coupled Brains of Captivated Audiences

Abstract: Abstract. Suspense not only creates a strong psychological tension within individuals, but it does so reliably across viewers who become collectively engaged with the story. Despite its prevalence in media psychology, limited work has examined suspense from a media neuroscience perspective, and thus the biological underpinnings of suspense remain unknown. Here we examine continuous brain responses of 494 viewers watching a suspenseful movie. To create a time-resolved measure of the degree to which a movie alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 85 publications
0
29
0
Order By: Relevance
“…This suggests that the cognitive and the emotional processing of reading suspenseful text may include components of identification with characters and the expectation of what will happen next in the narrative. Another fMRI study which investigated the brain dynamics of audiences watching a suspenseful movie revealed that the brain regions, during exposure to a suspenseful moment of a suspense film, were associated with emotional salience and higher cognitive processes (Schmälzle and Grall, 2020). This result indicated that the neural activity of viewing a suspenseful film could be related to the motivated attention and psychological tension.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…This suggests that the cognitive and the emotional processing of reading suspenseful text may include components of identification with characters and the expectation of what will happen next in the narrative. Another fMRI study which investigated the brain dynamics of audiences watching a suspenseful movie revealed that the brain regions, during exposure to a suspenseful moment of a suspense film, were associated with emotional salience and higher cognitive processes (Schmälzle and Grall, 2020). This result indicated that the neural activity of viewing a suspenseful film could be related to the motivated attention and psychological tension.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…As such, it has been connected to departure from the real world, enabling relaxation and renewal ( Belk and Costa, 1998 ). In contrast, a thriller induces an affective state associated with uncertainty regarding an emotionally significant event that motivates future-oriented prediction and the desire for resolution ( Lehne and Koelsch, 2015 ), creating strong psychological tension ( Schmälzle and Grall, 2020 ).…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Subjects with no available HADS data (N=3) were omitted from the relevant analyses. In addition to self-report measures, we made use of canonical suspense ratings previously collected as 21 subjects viewed the same 'Bang You're Dead' clip (25). To account for hemodynamic lag, we shifted the ratings backward by 2TRs (~5s; consistent with prior work in this domain (14)), removing the last two data points and imputing the first two with the mean of the first 5TRs of the original ratings.…”
Section: Self-report/behavioral Datamentioning
confidence: 99%